Rational Emotive Behavior Therapy to Overcome Social Anxiety in Santri Victims of Bullying - Abdul Jalil; Muhammad Bahrul Ulum Mubarok (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to examine the effectiveness of Rational Emotive Behavior Therapy in overcoming social anxiety in students who are victims of bullying in pesantren. This research focuses on how REBT can be applied to help overcome the social anxiety experienced by students who have been victims of bullying. This research uses a qualitative approach with a case study design to understand the emotional and social experiences of a santri with the initials ASN at Pondok Pesantren Darussalam Blokagung. Data were collected through in-depth interviews, participatory observation, and documentation. Data analysis was carried out by reduction, descriptive narrative presentation, and systematic conclusion drawing, complemented by triangulation for the validity of the results. The results showed that the systematic application of REBT can help students recognize, evaluate, and reconstruct irrational thoughts that are the root of social anxiety. REBT interventions are proven effective in reducing symptoms of social anxiety such as fear of interacting, low self-esteem, and withdrawal from the social environment. This study recommends the application of REBT as a counseling approach in the pesantren environment to support the mental health of santri in a sustainable manner.